Pengaruh konsep iman, Islam, dan ihsan terhadap perilaku seseorang - Ramadhani, Farid; Pratama, Dhuta Widya; Alqadir, Arifin; Faisol, Faisol (Maliki Interdisciplinary Journal, 2024)
This research explores the influence of the concepts of faith, Islam, and ihsan on a person’s behavior in everyday life. The aim of this research is to analyze how these three concepts contribute to forming good behavior and improving the spiritual quality of individuals. The research method used is a qualitative approach through literature review and analysis of relevant sources. Research findings show that iman (belief), Islam (obedience), and ihsan (perfection in worship) synergistically play an important role in forming good and ethical individual behavior. Iman provides a strong foundation of belief, Islam establishes a legal and ethical framework, while ihsan guides individuals towards perfection in every action. Further discussion explains the implications of applying these three concepts in everyday life, which includes relationships with Allah SWT, fellow humans, and the environment. This research contributes to the understanding of Islamic teachings and provides insight for individuals who wish to develop noble behavior through the application of the principles of faith, Islam and ihsan.